Neuromorphic Functions in PEDOT:PSS Organic Electrochemical Transistors. (12th October 2015) - Gkoupidenis, Paschalis; Schaefer, Nathan; Garlan, Benjamin; Malliaras, George G.
Abstract : Depressive short‐term synaptic plasticity functions are implemented with a simple polymer poly(3, 4ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) organic electrochemical transistor device. These functions are a first step toward the realization of organic‐based neuroinspired platforms with spatiotemporal information processing capabilities.